2006
DOI: 10.1111/j.1365-2044.2005.04440.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gel lubrication on cuff leakage of double lumen tubes during thoracic surgery*

Abstract: SummaryHigh-volume, low-pressure tracheal cuffs of disposable double lumen tubes may offer limited protection to the dependent lung if fluid leaks through folds in the inflated cuffs. This study was undertaken to determine the incidence of fluid leakage past the tracheal cuff and whether gel lubrication reduces the incidence. Fifty-five patients were randomly assigned to receive a double lumen tube with or without gel lubrication. The dependent lung was intubated. With the patient in the lateral position, meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Tube cuff lubrication has been used by several investigators during in vitro trials to imitate a close contact of the cuff surface with the tracheal mucosa and filling of microchannels (longitudinal folds) with mucosal fluid. In these models, cuff lubrication reduced or prevented fluid leakage past the cuff, results similar to those of our study [11,12]. The strength of the present study is the finding that cuff lubrication prevented fluid leakage even in those HVLP cuffs that have poor sealing characteristics.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Tube cuff lubrication has been used by several investigators during in vitro trials to imitate a close contact of the cuff surface with the tracheal mucosa and filling of microchannels (longitudinal folds) with mucosal fluid. In these models, cuff lubrication reduced or prevented fluid leakage past the cuff, results similar to those of our study [11,12]. The strength of the present study is the finding that cuff lubrication prevented fluid leakage even in those HVLP cuffs that have poor sealing characteristics.…”
Section: Discussionsupporting
confidence: 88%
“…Although earlier clinical studies [11,12] have reported a protective effect of gel lubrication in cuffed tubes against fluid leakage, the effect is only transient and is lost after 24-120 h. Because there is no reliable protection against subglottic leakage in clinical practice, gel lubrication should be avoided when investigating sealing qualities in HVLP tube cuffs by in vitro models. The difference in the sealing characteristics of tube cuffs becomes more conclusive and evident under the static unlubricated setup, which could facilitate tube selection for in vivo trials in the future.…”
Section: Discussionmentioning
confidence: 98%
“…However, if the wider academic community and professional historians in particular are to recognise the value of these contributions, then the review process for historical papers must be every bit as rigorous as that to which clinical and research papers are subjected. We read with interest the study by Sanjay et al about the effect of gel lubrication on fluid leakage past the tracheal cuff of double lumen tubes [1]. The authors present a good case for gel lubrication reducing fluid leakage past the cuff.…”
Section: Military Anaesthesiamentioning
confidence: 96%
“…Our monitoring system does not rely on comparing doctors with colleagues, but on comparing the performance of doctors with what can be achieved given an internationally recognised standard of risk-adjusted cardiac surgical performance (the logistic EuroSCORE) [1]. We believe therefore that our method is indeed criterion-based.…”
Section: A Replymentioning
confidence: 99%
See 1 more Smart Citation